2017
DOI: 10.3390/md15100313
|View full text |Cite
|
Sign up to set email alerts
|

Conotoxins as Tools to Understand the Physiological Function of Voltage-Gated Calcium (CaV) Channels

Abstract: Voltage-gated calcium (CaV) channels are widely expressed and are essential for the completion of multiple physiological processes. Close regulation of their activity by specific inhibitors and agonists become fundamental to understand their role in cellular homeostasis as well as in human tissues and organs. CaV channels are divided into two groups depending on the membrane potential required to activate them: High-voltage activated (HVA, CaV1.1–1.4; CaV2.1–2.3) and Low-voltage activated (LVA, CaV3.1–3.3). HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…Ca v 1.1–1.4 (L-type current) and Ca v 2.1–2.3 (P/Q, N, and R type) belong to the HVA group, while Ca v 3.1–3.3 (T-type current) to the LVA group. Between other functions, voltage-gated Ca 2+ channels are responsible for initiation of synaptic transmission, hormone secretion, and excitation-contraction coupling (Hille, 2001 ; Catterall, 2011 ; Ramirez et al, 2017 ).…”
Section: Xenopus Vs Mammalian Oocytes: Comparison Of Ion Chmentioning
confidence: 99%
“…Ca v 1.1–1.4 (L-type current) and Ca v 2.1–2.3 (P/Q, N, and R type) belong to the HVA group, while Ca v 3.1–3.3 (T-type current) to the LVA group. Between other functions, voltage-gated Ca 2+ channels are responsible for initiation of synaptic transmission, hormone secretion, and excitation-contraction coupling (Hille, 2001 ; Catterall, 2011 ; Ramirez et al, 2017 ).…”
Section: Xenopus Vs Mammalian Oocytes: Comparison Of Ion Chmentioning
confidence: 99%
“…The classification of knottins is based on criteria such as the gene superfamily, the pattern of cysteine bridging, and molecular targets [33,39]. ERVK CTXLP most resembles O-conotoxins (which encompass ω and γ conotoxin groups); these small toxic peptides act by blocking ion channels [40]. Inhibition of high-voltage activated Ca V 2.2 (N-type) calcium channels found at the presynaptic terminal of neurons by O-conotoxins, leads to suppressed acetylcholine release and neurotransmission [41].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of high-voltage activated Ca V 2.2 (N-type) calcium channels found at the presynaptic terminal of neurons by O-conotoxins, leads to suppressed acetylcholine release and neurotransmission [41]. The success of piscivorous cone snails to envenomate and immobilize their prey by blocking neuromuscular transmission is attributed to the efficacy of conotoxin peptides [34,40].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have confirmed that these bioactive venoms are a cocktail of neuroactive peptides, termed conopeptides or conotoxins, which can cause paralysis, shudder, and even death of the prey within seconds [ 1 , 5 ]. Subsequent research have revealed that conopeptides are able to selectively modulate voltage-gated ion channels [ 7 ] ( Table 1 ), including sodium channels [ 8 , 9 ], potassium channels [ 10 ], and calcium channels [ 11 , 12 ], as well as ligand-gated ion channels ( Table 1 ), such as nAChRs [ 13 , 14 , 15 ], serotonin receptor [ 16 ], NMDA receptor [ 17 ], GABA receptor [ 18 ], GPCRs [ 19 ] (α 1 -adrenoceptors [ 20 , 21 ], vasopressin receptor [ 22 ], neurotensin receptor [ 23 ]), and neurotransmitter transporters (noradrenaline transporter [ 21 , 24 ]), which are key targets for chronic diseases, like neuralgia [ 8 , 25 , 26 ], addiction [ 27 ], epilepsy [ 17 , 28 ], cancer [ 29 ], heart disease [ 30 , 31 ], and so on [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%